KEDUDUKAN UANG JEMPUTAN DALAM PERKAWINAN BAJAPUIK PADA MASYARAKAT MINANGKABAU PARIAMAN DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG - HIJRATUL MUSLIM (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Runtung 2. Idha Aprilyana 3. Muhd Yamin Adat Marriage Law is an inseparable part of the Indonesian Customary Law. In Marriage Customary Law, that of Minangkabau Pariaman in particular, is a form of marriage known as bajapuik marriage, which is taking marapulai (the prospective son in law) to the wedding held in the bride’s house by bringing certain condition namely proposal money. Nowadays, the development of bajapuik marriage has changed into consideration for the advantages and disadvantages in its implementation causing prosecution and proposal money repayment to either Religious Court or District Court. By the occurrence of these lawsuits, a study is required on proposal money as the marriage property as stipulated in Article 35 Section 1 and 2 the Law No. 1/ 1974 on Marriage that there is a classification of marital property namely joint property and pre-marriage property. The results based on the respondents comprehension and the interviews with LKAAM Padang Pariaman showed that the proposal money is essentially the initial capital for the couples in undergoing their marriage. Viewed from the process as stipulated in the Marriage Law No. 1/ 1974 defining pre-marriage property and joint property, the proposal money is classified into the pre-marriage property, yet viewed from the function, the proposal money belongs to joint property that is used for the sake of the couples. Over the time, bajapuik marriage nowadays influences the meaning and essence of the proposal money so that some grooms were found to only expect the proposal money from the marriage, as they thought considered the money their pre-marriage property. In fact, viewed from the adat (tradition), meaning and essence of the giving of the proposal money, it was given with aim to be their joint property. Keywords: Marriage property, Bajapuik Marriage, Proposal Money